The Role of microRNA in the Inflammatory Response of Wound Healing - Jiang, Yuanyuan; Xu, Xiang; Xiao, Long; Wang, Lihong; Qiang, Sheng (Frontiers in Immunology, 2022)
Wound healing, a highly complex pathophysiological response to injury, includes four overlapping phases of hemostasis, inflammation, proliferation, and remodeling. Initiation and resolution of the inflammatory response are the primary requirements for wound healing, and are also key events that determines wound quality and healing time. Currently, the number of patients with persistent chronic wounds has generally increased, which imposes health and economic burden on patients and society. Recent studies have found that microRNA(miRNA) plays an essential role in the inflammation involved in wound healing and may provide a new therapeutic direction for wound treatment. Therefore, this review focused on the role and significance of miRNA in the inflammation phase of wound healing.